Organizational and Business Innovations Brought by the SPED: An Empirical Study from the point of view of accountants and tax auditing bodies - Jordão, Ricardo Vinícius Dias; Silva, Milton Santos; Vasconcelos, Maria Celeste Reis Lobo; Brasil, Haroldo Guimarães (Revista de Administração da UFSM, 2019)
The research described in this article aimed to analyze the perception of accountants and federal and state tax auditing bodies in the metropolitan region of Belo Horizonte, Minas Gerais, on the adoption of the Public Digital Bookkeeping System (SPED). Data collection was done through a survey type research, based on a semi-structured questionnaire with open and closed questions. The results arising from the information of 98 respondents were subjected to quantitative and qualitative analysis, performed by the technique of content analysis. Our findings expand the knowledge on the subject helping to identify that the SPED increased the tax efficiency of the government and brought significant organizational impacts. This required that companies innovate in their corporate and business processes. All in all, the research findings show that SPED: (i) can be considered a milestone of the ’digital age’, (ii) represents a technological breakthrough which modernized the system of fiscal controls, (iii) led innovation in the practices of taxing and accounting bookkeeping, (iv) increased government access to business information, (v) caused cultural changes, (vi) required learning new methodologies and technologies, (vii) promoted improvements in compliance with accessory tax obligations, (viii) reduced the tax evasion and (ix) increased the revenues of the Government. It was also found that accountants and regulatory agencies need to better prepare for the use of SPED, which is an organizational and business innovation that is here to stay.